1996
DOI: 10.1097/00012272-199612000-00007
|View full text |Cite
|
Sign up to set email alerts
|

A Concept Analysis of Alcoholic Denial and Cultural Accounts

Abstract: Accounts are statements offered by individuals when explaining questionable behavior. Cultures vary in the kinds of accounts they honor, and individuals who deny a problem with alcohol may be attempting to maintain congruence between self and culture. Within this context, health care professionals who challenge a patient's denial may be causing unnecessary harm. The author presents a concept analysis of alcoholic denial in relation to the concept of accounts to explicate cultural variations in the manifestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Cultural differences between groups may provide one feasible explanation for the outcomes obtained in the present study. Wing 48 argued that what might be viewed as alcoholic denial within a subculture may actually serve to sustain congruence between an addict and his or her culture. Lalwani et al 35 suggested that people from more collectivist cultures engage in self-deception to maintain positive relationships with others, whereas individuals from culture that promote individualistic aspect seek self-honesty.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural differences between groups may provide one feasible explanation for the outcomes obtained in the present study. Wing 48 argued that what might be viewed as alcoholic denial within a subculture may actually serve to sustain congruence between an addict and his or her culture. Lalwani et al 35 suggested that people from more collectivist cultures engage in self-deception to maintain positive relationships with others, whereas individuals from culture that promote individualistic aspect seek self-honesty.…”
Section: Discussionmentioning
confidence: 99%
“…It is what people do when they are ill, as compared with what they should do as determined by a set of social standards (O'Connor, 1995;Wing, 1996). Leininger (1991) theorized that all cultures in the world have had a lay health care system, whether it be described as folk, indigenous, or generic.…”
Section: Overview Of Folk Healing Systemsmentioning
confidence: 99%
“…1 found much support for this conviction in my studies of alcoholism in several cultures. Native Americans and Hispanics perceived alcoholism as an unnatural illness placed on a victim by an evildoer or witch because of envy (Wing, 1996;Wing, Crow, & Thompson, 1995).…”
Section: Origins Of Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Para Shaffer e Simoneau (2001), a denegação do alcoolismo emerge perante a dor psíquica resultante da ambivalência, a qual reforça a resistência e conduz o dependente do álcool a optar pelo lado menos doloroso do seu conflito. Wing (1996), avança com a hipótese de que a denegação do alcoolismo poderá representar a tentativa de manter a congruência entre o self e o contexto cultural. O autor, desenvolveu um modelo de progressão da denegação da doença alcoólica constituído por cinco estágios, os quais, invariavelmente, terão que ser percorridos, para ultrapassar o fenómeno da denegação: (1) reacção ao acontecimento crítico; (2) desafiliação; (3) antecipação ambígua; (4) afiliação de pares e (5) aceitação.…”
Section: Introductionunclassified